New strategy toward a dual functional nanocatalyst at ambient conditions: influence of the Pd-Co interface in the catalytic activity of Pd@Co core-shell nanoparticles - Jain, Ruchi; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2018)
Bimetallic nanostructures with a combination of noble and nonnoble metals hold promise for improving catalyst activity and selectivity. Here, we report the synthesis of Pd@Co (PC) core shell morphology nanoparticles with three different ratios of palladium (Pd) and cobalt (Co), and a possibility to fine tune the ratio of core and shell thickness. PC exhibits superior and selective hydrogenation as well as oxidation catalytic activity at ambient or near-ambient conditions. Various characterization techniques have been employed to confirm the core shell morphology. Without any pre-treatment or activation, fresh catalysts with different Pd to Co ratios, that is, 2:1, 1:1, and 1:2, were subjected to olefin (phenylacetylene) hydrogenation and oxidation (styrene to styrene oxide) reaction. The catalytic activity results demonstrate that the 1:1 ratio of Pd/Co is the most active composition for controlled and stepwise reduction of phenyl acetylene to styrene and then to ethyl benzene; 1:1 Pd/Co shows 100% styrene conversion in 30 min. with an order of magnitude higher turnover frequency than other catalysts. The 1:1 PC ratio is also the most active composition for selective oxidation of styrene to styrene oxide. NAPXPS (near-ambient pressure XPS) results show that the active sites for catalytic hydrogenation and oxidation reaction are Co and Co3+, respectively. However, the superior catalytic performance can be attributed to Co (for reduction) or Co3+ (for oxidation), and the Pd Co interface plays a critical role in stabilizing the required functional character. NAPXPS results confirm that the superior catalytic performance can be attributed not only to Co or Co3+, but also to the Pd Co interface. The electronic effect and synergism between Co and Pd helps Co to stabilize in different oxidation states depending on the reaction conditions, and making it a dual functional catalyst.